The genus Persicaria (Polygonaceae) in Turkey with a new taxon record - Keskin, Mustafa; Severoğlu, Zeki (My University, 2020)
Polygonaceae family mainly introduces itself with its stipules called ochrea. In Flora of Turkey, this family is indicated by eight genera that include Atraphaxis, Pteropyrum, Calligonum, Rheum, Oxyria, Polygonum, Rumex, Emex. This article emphasizes that the genus Polygonum and Persicaria are utterly different from each other. Full names and distributions of the species of Persicaria in Turkey are given in detail. A new Persicaria taxon is also reported from Turkey. A diagnostic key for Persicaria has been created for the first time. The taxonomic status of the Persicaria leblebicii which was recently given as a new species, has been discussed.
Keywords: A new record, Polygonum, Persicaria, Polygonaceae, Turkey